The influence of intangible resources on the performance of agricultural cooperatives - Ishak, Suraiya; Omar, Ahmad Raflis Che (Asian Development Policy Review, 2023)
The purpose of this study is to investigate the relationship between intellectual capital (IC), which is represented by structural capital (SC), relational capital [RC], and human capital (HC), and member participation (MP) and performance within the context of agricultural cooperatives. This study employs a survey technique involving 104 palm oil smallholders’ cooperatives in Peninsular Malaysia, and the data are analyzed through the partial least squares (PLS) technique. The results indicate that MP and RC have a significant direct relationship with cooperatives’ financial performance. Simultaneously, MP also has a direct and significant relationship with the cooperatives’ non-financial performance. This proves that MP is the most important intangible resource that determines the cooperatives’ financial and non-financial performance. Members’ cooperation contributes through active involvement and sharing of constructive ideas, while RC contributes to the competitive advantages in cooperatives' business dealings. Meanwhile, SC and HC have non-significant relationships with cooperative performance. The findings confirm the postulation of the RBV that internal resources are useful to gain superior performance in the marketplace. Therefore, management of agricultural cooperatives must maintain good relationships with their members and relevant constituencies to ensure sustainable performance.